Perkembangan Kognitif Anak Usia Prasekolah 4-5 Tahun dengan Menggunakan Media Audio-Visual PowerPoint pada Siswa PAUD - Ni Dewi Eka Suwaryaningrat (Society, 2020)
This study aims to determine whether using PowerPoint audio-visual media can improve children’s cognitive development in ECE (Early Childhood Education) in North Tomohon Sub-District, North Sulawesi Province, Indonesia. The research method used was collaborative Classroom Action Research (CAR) conducted in ECE in North Tomohon Sub-District, and it was found that 1) Before using the PowerPoint audio-visual media, ECE in North Tomohon Sub-District still had difficulty doing the assigned tasks and answering teachers’ questions because the children cognitive was not stimulated well; 2) The use of PowerPoint audio-visual media can improve the child’s cognitive aspects because the learning activities were designed in an attractive, fun and not boring way. Through the use of PowerPoint audio-visual learning media, children’s cognitive can be stimulated well.